Neuropathologie und Ätiologie fokaler Epilepsien - Blümcke, Ingmar; Hamer, Hajo (Der Nervenarzt, 2012)
In 2010 the International League against Epilepsy published a new classification of epilepsies. A major advance of this classification system is the acknowledgment of a genetic or pathologic-anatomic basis of epilepsy as important predictors of outcome (cause matters). This applies in particular to structural-metabolic lesions, which were frequently recognized in surgical specimens obtained from patients with drug-resistant focal epilepsy, i.e. hippocampal sclerosis, glioneuronal tumors, focal cortical dysplasias, vascular malformations, ischemia, intracerebral hemorrhage, glial scars or inflammation. A better understanding and classification of the etiopathology as well as the underlying molecular mechanisms will help to anticipate and appreciate the clinical course of a disease as well as to develop new and targeted drug treatment. Surgically available human brain tissue will be most helpful to support this approach but will also need careful neuropathological evaluation with accurate classification systems and use of terminology. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain tumors; Dysplasia; Hippocampal sclerosis; Seizure